Analisis Kualitas Terjemahan Otomatis Subtitle Pada Channel Youtube (Indo4arab Khalid Nahdi) - Riantika Zahara; Zamzam Nurhuda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
In the current era, translation plays a crucial role in developing knowledge and technology across various fields. The essence of translation is to convey messages, ideas, thoughts, and emotions from the source language to the target language. This research provides benefits from both theoretical and practical perspectives. Theoretically, this research is expected to enhance knowledge and understanding in translation from Arabic to Indonesian. The qualitative research method used in this study involves collecting and analyzing descriptive data in the form of observable words and behaviours. This study successfully interprets natural linguistic phenomena by utilizing listening, note-taking, and observing the transcripts of Khalid Nahdi's YouTube videos. Based on the analysis of 20 automatic subtitles in the YouTube video